Serum IgE Levels Are Associated With the Prognosis of Minimal Change Disease - Li, Heng; Wang, Lefeng; Li, Xiayu; Chen, Wenqing; Zhang, Ying; Chen, Jianghua (Frontiers in Immunology, 2022)
Background Previous reports showed that some patients with minimal change disease (MCD) had high serum immunoglobulin E (IgE) levels. This study aimed to explore the proportion of MCD patients with high serum IgE levels and evaluate the correlation between serum IgE levels and MCD remission and relapse. Methods This study enrolled 222 new-onset patients with renal biopsy-confirmed MCD from October 2012 to October 2019 at the First Affiliated Hospital of Zhejiang University in Hangzhou, China. Patients’ demographics and clinical parameters were analyzed. Results The results indicated that 70.3% of 222 MCD patients had high serum IgE levels (IgE > 100.0 IU/mL). Moreover, 134 patients were treated with glucocorticoids alone and divided into the low- and high-IgE groups, according to the median serum IgE level (523.5 IU/mL). The mean time to complete remission of the low- and high-IgE groups was 29.0 ± 2.2 and 45.7 ± 4.2 days, respectively (log-rank test; P = 0.002). The mean time to total remission was 19.1 ± 1.4 and 31.6 ± 3.2 days of the low- and high-IgE groups, respectively (log-rank test; P < 0.001). The mean time to first relapse in the low- and high-IgE groups was 701.2 ± 65.0 and 425.0 ± 52.6 days, respectively (log-rank test; P = 0.002). Serum IgE ≥ 523.5 IU/mL was an independent correlation factor affecting the patients’ remission and relapse. Conclusion Serum IgE level was an independent correlation factor for MCD remission and relapse. MCD patients with high serum IgE levels were prone to delayed remissions and early relapses.